EFFECT OF SUPERVISED MODERATE INTENSITY EXERCISE PROGRAM IN PHASE ONE CARDIAC REHABILITATION OF POST OPERATIVE CABG PATIENTS - A RANDOMIZED CONTROLLED TRAIL (International Journal of Physiotherapy, 2014)
Background: With the increasing number of cases for CABG, the cardiac rehabilitation has gained importance. The trends in rehabilitation of a coronary artery disease patient are changing by incorporating a variety of aerobic exercises and resisted training in to their rehabilitation program. The outcome of any exercise chiefly depends on the training parameters like intensity, frequency and duration. Hence the present study focused to know the effects of supervised moderate intensity exercises on patients during hospital discharge following CABG. The objective of is to study the effectiveness of supervised moderate intensity exercise on distance walked and Quality of Life at hospital discharge following CABG.Methods: Study recruited randomly 46 patients between age group 40-65 years who were posted for non-emergency CABG for the first time. Pre-operative assessment was done thoroughly and was divided in to two groups, Group A conventional treatment and Group B Moderate intensity exercise group. The patients were treated using different protocols in terms of intensity for 8-10 days immediate post CABG. Then the outcome parameters of 6MWT and sf-36 were compared for analysis.Results: Both groups individually showed extremely significant results for two outcome measures. 6 MWD difference between two treatment groups showed significant results with unpaired t test (t = 8.5720,p